2022
DOI: 10.1016/j.jrp.2021.104186
|View full text |Cite
|
Sign up to set email alerts
|

Open laptops, open minds: Consensus and accuracy in big five personality perception from laptop stickers

Abstract: Manuscript under review; cite at own risk HighlightsExamined people's abilities to judge others' traits from their laptop stickers Compared traditional methods to cross-classified structural equation models (CC-SEMs) All Big Five traits except negative emotionality showed adequate consensus CC-SEM-based accuracy was significant only for extraversion and openmindedness Number of stickers served as a cue for the accuracy effect of aesthetic sensitivity Highlights (for review

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Third, this work has implications for perceptual accuracy because both men and women were significantly accurate in the self-ratings of their own physical attractiveness based on others' observations of the same (even after controlling for their partner's self-reported physical attractiveness). Indeed, people may be as accurate in their self-views of physical attractiveness as they are in accurately gauging others' personality traits (e.g., Campbell et al, 2022;Gosling et al, 2002).…”
Section: Methodological and Theoretical Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, this work has implications for perceptual accuracy because both men and women were significantly accurate in the self-ratings of their own physical attractiveness based on others' observations of the same (even after controlling for their partner's self-reported physical attractiveness). Indeed, people may be as accurate in their self-views of physical attractiveness as they are in accurately gauging others' personality traits (e.g., Campbell et al, 2022;Gosling et al, 2002).…”
Section: Methodological and Theoretical Implicationsmentioning
confidence: 99%
“…We fit an APIM to the six meta-analytic weighted-mean correlations, which regressed men's and women's observed physical attractiveness on their own and their partner's self-reported physical attractiveness. 7 Although we explore alternative models below, an APIM is consistent with person-perception lens models in which a criterion (observed physical attractiveness) is regressed onto a perception of the same construct (self-reported physical attractiveness; e.g., Campbell et al, 2022;Gosling et al, 2002).…”
Section: Actor-partner Interdependence Modelmentioning
confidence: 99%
“…Research has shown a connection between self-reported personality and photos based on different photographs, such as standard photographs and spontaneous photographs (e.g., Naumann et al, 2009 ; Nestler et al, 2012 ; Cooper et al, 2020 ; Campbell et al, 2022 ). For example, Naumann et al (2009) coded the participants’ spontaneous photographs and found that extraversion was positively associated with smiling.…”
Section: Background Researchmentioning
confidence: 99%